2020
DOI: 10.1186/s13578-020-00454-8
|View full text |Cite
|
Sign up to set email alerts
|

Inverse correlation between Interleukin-34 and gastric cancer, a potential biomarker for prognosis

Abstract: Background Gastric cancer (GC) is a malignancy with high morbidity/mortality, partly due to a lack of reliable biomarkers for early diagnosis. It is important to develop reliable biomarker(s) with specificity, sensitivity and convenience for early diagnosis. The role of tumour-associated macrophages (TAMs) and survival of GC patients are controversial. Macrophage colony stimulating factor (MCSF) regulates monocytes/macrophages. Elevated MCSF is correlated with invasion, metastasis and poor surviva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 44 publications
5
20
0
Order By: Relevance
“…Unfortunately, no correlation with survival of GC patients was observed among any combination of IL-31, IL-32 and IL-33 expression, a similar result that we have reported previously for the relationship between IL-34 in GC [30]. Such a discrepancy among IL-31, 32, 33 and 34 may be due to different receptors and/or signalling pathways, which will be clari ed in the conditioning knockout mice in future studies.…”
Section: Discussionsupporting
confidence: 67%
“…Unfortunately, no correlation with survival of GC patients was observed among any combination of IL-31, IL-32 and IL-33 expression, a similar result that we have reported previously for the relationship between IL-34 in GC [30]. Such a discrepancy among IL-31, 32, 33 and 34 may be due to different receptors and/or signalling pathways, which will be clari ed in the conditioning knockout mice in future studies.…”
Section: Discussionsupporting
confidence: 67%
“…In gastric cancer, both IL‐34/TAM and CSF‐1/TAM could be used as potential good prognosis biomarkers since they are down‐regulated in cancer cells 92 . However, a team demonstrated the ability of CSF‐1 to promote proliferation, migration, and apoptosis resistance in a gastric cell line 93 .…”
Section: Overlapping and Non‐overlapping Functions Of Il‐34 And Csf‐1 In Diseasesmentioning
confidence: 99%
“…There were 1.76 million lung cancer deaths in 2018, accounting for nearly one-fifth of all cancer deaths (31,32). Several studies have confirmed that IL-34 is related to tumors, but few studies have investigated IL-34 in LUAD (15,18,20). Thus, we conducted a study based on existing data to explore the prognostic value of IL-34 in patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…IL-34 has also been confirmed to be associated with the progression of ovarian cancer (17). IL-34 can promote cancer in a variety of solid tumors such as gastric cancer, colorectal cancer, liver cancer, and breast cancer (18)(19)(20)(21). In addition to promoting tumor metastasis, IL-34 can also inhibit tumor differentiation and migration.…”
Section: Introductionmentioning
confidence: 98%